Synthesis and SAR Study of Simple Aryl Oximes and Nitrofuranyl Derivatives with Potent Activity Against Mycobacterium tuberculosis - da Costa, Cristiane França; de Souza, Marcus V. N.; da Silva Lourenço, Maria C.; Coimbra, Elaine Soares; da Silva Lourenço Carvalho, Guilherme; Wardell, James; Calixto, Stephane Lima; da Trindade Granato, Juliana (Letters in Drug Design & Discovery, 2020)
Background: Oximes and nitrofuranyl derivatives are particularly important compounds in medicinal chemistry. Thus, many researchers have been reported to possess antibacterial, antiparasitic, insecticidal and fungicidal activities. Methods: In this work, we report the synthesis and the biological activity against Mycobacterium tuberculosis H37RV of a series of fifty aryl oximes, ArCH=N-OH, I, and eight nitrofuranyl compounds, 2-nitrofuranyl-X, II. Results: Among the oximes, I: Ar = 2-OH-4-OH, 42, and I: Ar = 5-nitrofuranyl, 46, possessed the best activity at 3.74 and 32.0 μM, respectively. Also, 46, the nitrofuran compounds, II; X = MeO, 55, and II: X = NHCH2Ph, 58, (14.6 and 12.6 μM, respectively), exhibited excellent biological activities and were non-cytotoxic. Conclusion: The compound 55 showed a selectivity index of 9.85. Further antibacterial tests were performed with compound 55 which was inactive against Enterococcus faecalis, Klebisiella pneumonae, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella typhymurium and Shigella flexneri. This study adds important information to the rational design of new lead anti-TB drugs. Structure-activity Relationship (SAR) is reported.
Keywords: cytotoxicity